DEVELOPMENT OF SOCIAL ENTREPRENEURSHIP IN KAZAKHSTAN (Journal of Economic Research & Business Administration, 2018)
Job creation is one of the important stages in eliminating poverty in the world, and in this directionthe most successful and competitive institution is social entrepreneurship. Defining the essence of socialentrepreneurship, we can say that social entrepreneurship is an activity aimed at solving social problemsby finding new or additional resources and a new way of applying them through the synergy of the opportunitiesof society, business and the state, the synergy of social and entrepreneurial activity. Socialentrepreneurship connects the social purpose of the organization with entrepreneurial innovation andthe achievement of sustainable self-sufficiency. Social entrepreneurship is an institutionally mature formof intersectoral partnership in which the state, business and non-profit organizations find ways of cooperatingto solve social problems. In Kazakhstan, this is a fairly young phenomenon, but there is already asuccessful practice. At the same time, at this stage, the degree of scientific elaboration of the problems ofthe development of social entrepreneurship in Kazakhstan lags far behind the practice. Therefore, in general,there is a simplified representation and misunderstanding of the nature of social entrepreneurship onthe part of the state and business, the difficulties of legislative and administrative promotion of the idea.